Deformation and Energy Absorption Characteristics of Metallic Thin-Walled Tube with Hierarchical Honeycomb Lattice Infills for Crashworthiness Application - Shahrukh Alam; Mohammad Uddin; Colin Hall (Metals, 2025)
This paper investigates the axial deformation characteristics and crashworthiness of thin-walled metal tubes (TWT) reinforced with Polyetherketoneketone (PEKK) honeycomb lattice structures consisting of bio-inspired hierarchical cellular topological features. Experimentally validated numerical results revealed that the specific energy absorption capacity (SEA) of these composite structures increased with filler volume corresponding to a specific cellular topology. This includes the bio-inspired hierarchical sparse (BHS) topology, which registered a remarkable improvement in SEA over the hollow tube of 202%. In contrast, the central (BHC) topology deformed in an unstable hex-dominated pattern and triggered catastrophic failure of the composite in global bending mode. Furthermore, rigid cells were shown to drastically increase the initial peak force (IPF), while cells with low stiffness were beneficial for maintaining a low level of IPF and moderately improving SEA. Moreover, the rib and wall thickness of the BHS honeycomb cells were suitably tailored to increase the SEA by 2.1%, while simultaneously reducing the IPF by 3.7%. These findings suggest that multi-functional mechanical attributes of PEKK hierarchical honeycomb lattice fillers can mutually benefit thin-walled tubes with superior energy absorption capability and lightweight features over conventional lattice-filled tubes or a hollow tube.